Seismic Performances of Replaceable Steel Connection with Low Yield Point Metal - Haoxiang He; Kui Chen; Ruifeng Li (Advances in Materials Science and Engineering)
Compared with the traditional steel rigid connection, the beam-column connections with weakened beam end have better ductility, but the local buckling in the weakened zone and the overall lateral deformation may occur in strong earthquake. The replaceable steel connection with low yield point metal is proposed based on the concept of earthquake resilient structure. In this connection, the weakened parts in the flange slab and web plate are filled with low yield point metal, and the metal firstly yields and dissipates energy sufficiently in earthquake; hence, the main parts are intact and the yield point metal can be replaced. The seismic performances of the three types of connections which include traditional connection, beam end weakened connection, and replaceable connection with low yield point steel under low cycle reciprocating load are studied. In addition, the energy dissipation capacity and damage characteristics of different connections are compared. The multiscale finite element models for the steel frames with different connections are analyzed by time-history method; both the computational efficiency and the accuracy are assured. The analysis results approve that the replaceable connection can confine the major damage in the replacement material and have better energy dissipation ability, safety reserves, and resilient ability.